Penggunaan Gadget di Kalangan Siswa SMP Insan Kamil Kota Bogor terhadap Interaksi Sosial - Airlangga Auliarachman Diadi; Iwan Sukoco (Jurnal Indonesia Sosial Sains, 2022)
In this era technology has become the field most widely used by the wider community, one of the most widely used technology fields is the internet. The advantages of the internet can be used by many people, even these users have urged their users to switch. For example, in this era a lot of business is done using the internet. The use of the internet is not solely for marketing but far from that companies use it even to the stage of buying and selling transactions. However, the convenience of the internet also makes business people have many competitors that have sprung up, so that in this day and age companies are not only tasked with attracting consumers but also must make consumers loyal. So that consumers do not switch to competing companies, companies need to meet customer satisfaction and also make consumers believe. This study aims to examine the effect of the service user interface, service information quality, perceived security, E-commerce service feedback on the satisfaction, trust, and loyalty of Agoda customers in Indonesia. The population used in this study is people who have made transactions in the Agoda application at least 2 times. The data used is primary data with the number of respondents as many as 166 people. The sampling technique used in this study is convenience sampling. As for the analysis using the SEM method and processed using the AMOS program. The results showed that the eleven hypotheses in this study were significant. User interface service quality, information quality, feeling of security, E-commerce service feedback, electronic customer satisfaction, and electronic customer trust have a positive effect on E-commerce customer loyalty.